Platelet Endothelial Aggregation Receptor 1 Polymorphism Is Associated With Functional Outcome in Small-Artery Occlusion Stroke Patients Treated With Aspirin - Li, Zhizhang; Jiang, Huayu; Ding, Ying; Zhang, Dong; Zhang, Xiaoguang; Xue, Jie; Ma, Ruinan; Hu, Liang; Yue, Yunhua (Frontiers in Cardiovascular Medicine, 2021)
BackgroundThe role of genetic polymorphisms is important in defining the patient’s prognosis and outcomes in coronary artery disease. The aim of the present study was to explore the association between PEAR1 rs12041331 polymorphism and the outcomes in patients with acute ischemic stroke that are treated with aspirin or dual antiplatelet therapy(DAPT)with clopidogrel. MethodsA total of 868 ischemic stroke patients who were admitted to our hospital from 01/01/2016 to 12/30/2018 were retrospectively studied. Stroke subtypes were defined by the Trial of Org 10172 in Acute Stroke Treatment(TOAST)classification. These patients were treated with aspirin alone or DAPT. The genotype distribution of PEAR1 rs12041331 SNP(AA, AC and CC) between different TOAST subtypes and treatment groups was assessed, and the clinical impact of genetic variants on functional outcomes defined by National Institutes of Health Stroke Scale(NIHSS), modified Rankin Scale(mRS)and Barthel Index(BI)was analyzed using univariate and multivariate logistic regression models. ResultsAmong 868 stroke patients, PEAR1 AA genotype was 16%, GA was 47% and GG was 36%. 44% had aspirin alone and 56% had DAPT. Overall, the distribution of PEAR SNP was not significant among two treatment groups or subtype of TOAST. In contrast, in patients treated with aspirin alone, PEAR1 AA tended to be higher in small-artery occlusion (SAO) subtype when compared to no-lacunar subtype including cardioembolism (CE) and large-artery atherosclerosis(LAA). PEAR1 AA genotype was significantly associated with favorable functional outcomes at day 7 and discharge only in SAO patients treated with aspirin alone compared with GG genotype. Multivariate regression models further suggested that AA genotype was independently associated with favorable outcomes in this group after adjusted for three common stroke risk factors such as age, hypertension history and C-reactive protein level (OR 0.23, 95% C.I., 0.07-0.64, P=0.02 for seven-day NIHSS; OR 0.2, 95% C.I., 0.06-0.66, P=0.03 for seven-day mRS and OR 0.25, 95% C.I., 0.08-0.72, P=0.03 for seven-day BI, respectively) Conclusion The impact of PEAR1 rs12041331 polymorphism on aspirin depends on TOAST subtype. PEAR1 AA carrier with SAO stroke is most sensitive to aspirin therapy. PEAR1 AA is an independent factor for the short term functional outcomes in SAO patients treated with aspirin alone.